The first comprehensive database of germline pathogenic variants in East Asian cancer patients. (29th December 2021) - Shi, Xiaoshun; Li, Ruidong; Zhai, Jianxue; Chen, Allen Menglin; Huang, Kailing; Zheng, Zhouxia; Chen, Zhuona; Dong, Xiaoyin; Liu, Xiguang; Lu, Di; Feng, Siyang; Diao, Dingwei; et al.
Abstract: Pathogenic germline variants in cancer-associated genes are risk factors for cancer predisposition. However, systematic mining and summarizing of cancer pathogenic or likely pathogenic variants has not been performed for people of East Asian descent. This study aimed to investigate publicly available data to identify germline variants in East Asian cancer cohorts and compare them to variants in Caucasian cancer cohorts. Based on the data we retrieved, we built a comprehensive database, named COGVIC (Catalog of Germline Variants in Cancer). A total of 233 variants in the East Asian population were identified. The majority (87%) of genes with cancer-associated variants were not shared between the East Asian and Caucasian cohorts. This included pathogenic variants in BRCA2 . Our study summarized the prevalence of germline variants in East Asian cancer cohorts and provides an easy-to-use online tool to explore germline mutations related to cancer susceptibility. Database URL: http://www.cogvic.vip/